Executive Compensation: A Multidisciplinary Review of Recent Developments - Devers, Cynthia E.; Cannella, Albert A.; Reilly, Gregory P.; Yoder, Michele E. (Journal of Management, 2007)
The failure to document a consistent and robust relationship between executive pay and firm performance has frustrated scholars and practitioners for over three quarters of a century. Although recent compensation research has revealed alternative theoretical frameworks and findings that hold the potential to significantly improve our understanding of executive compensation, to date this diverse literature lacks theoretical integration. Accordingly, we develop a framework to organize and review these recent findings. We further identify methodological issues and concerns, discuss the implications of these concerns, and provide recommendations for future research aimed at developing a more integrated research agenda.